(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Foreign material used in ocular surface surgery may lead to local complications such as discomfort, scarring, or infection. Plasma-derived products such as fibrin glue may produce hypersensivity reactions whereas the risk of viral transmission remains. We describe a simple method of achieving conjunctival autograft adherence during pterygium surgery avoiding potential complications associated with the use of fibrin glue or sutures. Materials & Methods: This study was conducted at Jahurul Islam Medical college Hospital, Bajitpur, Kishoregonj from August 2016 to April 2018. Fifty cases with unilateral primary pterygium were selected for the study. The operation was done under local anaesthesia. After pterygium excision and fashioning of the autologus conjunctival graft, the recipient bed is allowed to achieve natural haemostasis and relative dessication before graft placement. Excessive haemorrhage in the graft bed is temponaded. Graft adherence and positioning is examined after surgery. Results: A total of 50 eyes of 50 patients mean age at the time of surgery was 40.5±10.3 years ranged from 17 to 70 years, with a female to male ratio was 1:1.94, underwent sutureless glue-free autologus conjuntival graft after pterygium excision. Mean graft area was 24(1.5) mm2. The patients were followed up for 4 months. Cosmesis was excellent in all cases and there were no intra- or post-operative complications requiring further treatment. Conclusion: This simple technique for pterygium surgery may prevent potential adverse reactions encountered with the use of foreign materials and this small series provided safe and comparable results to current methods. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 28-31